Acceptability Test and Nutrient Analysis of Yellow Sweet Potato Flour Biscuits (Ipomoea Batatas L.) and Catfish Flour (Clariidae) As An Alternative to Complementary Feeding - Desnada Nabila Hanun; Jonni Syah R.Purba; Ayu Rafiony (Universitas Negeri Semarang, 2024)
Background: Complementary feeding can help children accept a variety of foods, improve chewing and swallowing, and adapt to new foods. One of the options for complementary feeding is biscuits that can be made from yellow sweet potato flour and catfish meal. Yellow sweet potatoes contain B-carotene and carbohydrates, while catfish are rich in protein, fat, and calcium. Objective: To determine the acceptability and analysis of the nutritional content of yellow sweet potato flour biscuits and catfish meal as an alternative to complementary feeding. Method: This study used an experimental process that used three formulations: F1 (95% yellow sweet potato: 5% catfish), F2 (80% yellow sweet potato: 20% catfish), and F3 (65% yellow sweet potato): 35% catfish). The test is carried out through 2 stages, namely the organoleptic test and the nutrient test, which includes protein, fat, carbohydrates, and calcium. Results: The results showed that three formulations, F1 (95% yellow sweet potato: 5% catfish), F2 (80% yellow sweet potato: 20% catfish), and F3 (65% yellow sweet potato: 35% catfish) were the most preferred by the panelists was F2 (80% yellow sweet potato: 20% catfish). The results of the nutrient content in the most preferred formulation are F2 (80% yellow sweet potato: 20% catfish) which was carried out in the laboratory of the Pontianak State Polytechnic, namely, protein 9.09%, fat 28.2%, carbohydrate 47.35%, and calcium 8.33%. Conclusion: Biscuits affect color, aroma, and texture with the formulation of yellow sweet potato flour and catfish meal, with no effect on taste